Energy and Poverty in Africa - Kauffmann, Céline (OECD Development Centre Policy Insights, 2005)
Access to energy is essential for economic, social and political development. Despite its enormous potential in fossil and renewable energy sources, Africa suffers from major energy deficits. The continent's resources are underexploited or exported in raw form or wasted in the course of extraction or transport. As a result, supplies available for local populations are largely insufficient and energy consumption is essentially reliant on biomass